Pengaruh Role Stress pada Turnover Intentions Konsultan Pajak dengan Kompensasi Sebagai Variabel Pemoderasi - Himawantara, I Gusti Agung; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 22 No 3 (2018)DO - 10.24843/EJA.2018.v22.i03.p01, 2018)
This research was conducted in order to obtain evidence of how the influence of role stress on turnover intentions of tax consultant in Tax Consultant Office in Denpasar City with compensation as moderator varable. This research was conducted at 15 Tax Consultant Office in Denpasar City. The number of samples obtained was 112 respondents by using purposive sampling sampling technique. The data were collected using questionnaire method. The hypothesis was tested using technique of Moderating Regression Analysis (MRA). Based on the result of the research, it is known that role conflict and role ambiguity have positive effect on turnover intentions, but role overload has no significant effect on turnover intentions. Based on the research that has been done also known that compensation can weaken the influence of role conflict and role ambiguity on turnover intentions but can not moderate the influence of role overload on turnover intentions. Keyword: Turnover Intentions, Role Conflict, Role Ambiguity, Role Overload, Compensation.